2001
DOI: 10.1007/s004970000063
|View full text |Cite
|
Sign up to set email alerts
|

In vitro double fertilization in Nicotiana tabacum (L.): the role of cell volume in cell fusion

Abstract: The role of cell volume in regulating cell fusion was investigated by in vitro fertilization to elucidate mechanisms involved in double fertilization. The results revealed that in our model gamete fusion was more efficient than the fusion of somatic cells under the same conditions. The fusion of selected mesophyll protoplasts of different sizes and their fusion with chloroplasts demonstrated that cell volume ratio played a role in this process: as the ratio increased, fusion was more efficient and faster. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This consistency suggests that positionally pre-determined regions are present on the surface of the egg cell and the central cell, and these regions are responsible for ''receiving'' the sperm cells. Recent studies using in vitro methods (Kranz 2001;Sun et al 2001) to study plant fertilization should further our understanding of the mechanism of gamete fusion in flowering plants.…”
Section: Discussionmentioning
confidence: 99%
“…This consistency suggests that positionally pre-determined regions are present on the surface of the egg cell and the central cell, and these regions are responsible for ''receiving'' the sperm cells. Recent studies using in vitro methods (Kranz 2001;Sun et al 2001) to study plant fertilization should further our understanding of the mechanism of gamete fusion in flowering plants.…”
Section: Discussionmentioning
confidence: 99%
“…The greater apparent efficiency of gamete-to-gamete fusion has also been challenged. Recently, Sun et al (2001), fusing somatic cells (and even chloroplasts) with cells of various sizes, found that efficiency of fusion in each size class did not appear to differ with that found in male gamete lineage cells of similar size. Disparities in volume could also be a mechanism for preferentiality during fertilization when sperm cells differ in volume (Tian et al 2001).…”
Section: Adhesion and Characteristics Of In Vitro Fusionmentioning
confidence: 95%
“…Attempts to combine dicot gametes have met with some success in Nicotiana tabacum. (Sun et al 1995(Sun et al , 2000(Sun et al , 2001Tian & Russell 1997b). In each of these cases, fusion has been stimulated using chemical means with polyethylene glycol (PEG).…”
Section: Adhesion and Characteristics Of In Vitro Fusionmentioning
confidence: 98%
“…Individual isolated gametes have been fused electrically (e.g., Kranz et al 1991Kranz et al , 1998Kovács et al 1995;Uchiumi et al 2007b) and chemically, by calcium Faure et al 1994;Digonnet et al 1997;Kranz et al 1998;Antoine et al 2000;2001b;Khalequzzaman and Haq 2005) or by polyethyleneglycol (e.g., Sun et al 1995Sun et al , 2000Sun et al , 2001Tian and Russell 1997). The fusion method which uses electrical pulses is well established and efficiently Fig.…”
Section: Techniques Of In Vitro Fusion Of Defined Gametesmentioning
confidence: 98%